Fasciculus moralitatis Omelie morales de infantia Saluatoris - of Heisterbach, Caesarius (Karolinum Press, 2023)
Primarily known as the author of the Dialogus miraculorum-a collection of exemplary stories that won Caesarius his reputation as the master of Cistercian storytelling-Caesarius of Heisterbach's strong predilection, however, seems to have been for writing sermons and homilies. Although they are not as well known today, his Homilies on Jesus' Childhood are exceptional in many ways. Readers will immediately notice Caesarius's versatility, as he employs an impressive array of persuasive techniques (quoting scholarly works, interpreting Hebrew names and letters, delving into etymology and numerology), as well as including numerous exempla to instruct both the learned and the simple.